EVALUASI WEBSITE PORTAL PROVINSI SUMATERA SELATAN PADA DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA - Fendri Martadinata (jurnal kesehatan terapan sains dan teknologi, 2023)
Abstract : With the development of information technology, it is hoped that it will become the most effective medium for finding and disseminating information. Based on Presidential Instruction No. 3 of 2003 concerning national policies and strategies for e-government development and the decision of the minister of state for communication and information number: 12/SK/MENEG/KI/2002 dated March 1, 2002 concerning the establishment of an e-government development task force in each government agency Republic of Indonesia. A website needs to be measured in terms of ease of learning, ease of use, satisfaction and efficiency, for the continuity and development of the website in the future. This measurement can use usability testing or usability testing. In this study, taking the object, namely the website of the Department of Transportation, Communication and Information Technology, the results of this usability testing will produce an assessment of the site and provide input in the website development process in the future. Based on the descriptions above, the writer intends to raise these problems as research material for thesis. The title chosen is "South Sumatra Provincial Government Portal Website Evaluation at the Department of Transportation, Communication and Informatics"